51-7x=12+(-4x)

Simple and best practice solution for 51-7x=12+(-4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 51-7x=12+(-4x) equation:


Simplifying
51 + -7x = 12 + (-4x)

Solving
51 + -7x = 12 + (-4x)

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '(4x)' to each side of the equation.
51 + -7x + (4x) = 12 + (-4x) + (4x)

Combine like terms: -7x + (4x) = -3x
51 + -3x = 12 + (-4x) + (4x)

Combine like terms: (-4x) + (4x) = 0
51 + -3x = 12 + 0
51 + -3x = 12

Add '-51' to each side of the equation.
51 + -51 + -3x = 12 + -51

Combine like terms: 51 + -51 = 0
0 + -3x = 12 + -51
-3x = 12 + -51

Combine like terms: 12 + -51 = -39
-3x = -39

Divide each side by '-3'.
x = 13

Simplifying
x = 13

See similar equations:

| 2x+3+5x=13 | | 5+3(n+9)=-3 | | 5+x-3[x+4]=-17 | | f(x)=2x+x-1 | | 3n-13=n+6 | | (x+5)(x-5)(x-7)=0 | | x^2+8x-7=8 | | 16x+18y+10x-7y= | | 5y^2+8y= | | 3k-2=39 | | 5X^3/(10x^2+5x) | | 5=-5+2x | | -x+3x-9=5 | | 9x+6-8=-38 | | 4x-3+2x+5=20 | | 15/2=5w | | 5x^3/10x^2+5x | | 5.00+0.8x=14.6 | | 5+8x=14.6 | | 3(10+-2y)+4y=8 | | 3-(4b-2)=3-4b-2 | | -4x-3=-6x-9 | | (8-x)+4=0 | | 5x+646464646464644646464646464644664464646464645554987604596=3 | | m^2-8m+16/5m^2+m | | 10+3x=2x-8x+40 | | y=-0.25x | | -12=39-6 | | x+2-9102301+78xypn-9087px=-12123 | | y=-0.25 | | 4a+1.5=13.5 | | -1=3(x-4) |

Equations solver categories